A Model‐Based Workflow to Benchmark the Clinical Cholestasis Risk of Drugs. Issue 5 (28th September 2021) - Baier, Vanessa; Clayton, Olivia; Nudischer, Ramona; Cordes, Henrik; Schneider, Annika R. P.; Thiel, Christoph; Wittenberger, Timo; Moritz, Wolfgang; Blank, Lars M.; Neumann, Ulf P.; Trautwein, Christian; Kelm, Jens; et al.
Abstract : We present a generic workflow combining physiology‐based computational modeling and in vitro data to assess the clinical cholestatic risk of different drugs systematically. Changes in expression levels of genes involved in the enterohepatic circulation of bile acids were obtained from an in vitro assay mimicking 14 days of repeated drug administration for 10 marketed drugs. These changes in gene expression over time were contextualized in a physiology‐based bile acid model of glycochenodeoxycholic acid. The simulated drug‐induced response in bile acid concentrations was then scaled with the applied drug doses to calculate the cholestatic potential for each compound. A ranking of the cholestatic potential correlated very well with the clinical cholestasis risk obtained from medical literature. The proposed workflow allows benchmarking the cholestatic risk of novel drug candidates. We expect the application of our workflow to significantly contribute to the stratification of the cholestatic potential of new drugs and to support animal‐free testing in future drug development.